AWARENESS ABOUT THE MANAGEMENT OF AVULSED TOOTH AMONG DENTAL STUDENTS (Journal of Pharmaceutical Negative Results, 2022)
AIM: To assess the level of awareness and also to create awareness about the management of avulsed tooth among dental students.BACKGROUND: The complete displacement of a tooth from its socket due to accidental or non accidental injuries that may cause loss of healthy teeth is termed as the tooth avulsion. Success of tooth replantation depends on extraalveolar dry time, storage media, type of retention, time of endodontic treatment, type of drug prescribed, oral hygiene status of the victim as well as the general health.Preventing the dehydration of the avulsed tooth and also minimizing the root manipulation are very important for preserving the periodontal ligament cells.MATERIALS AND METHOD: A questionnaire was prepared,comprising 13 questions with the sample size of 100 dental students.The results were analyzed using SPSS version 23 and the method of representing each output variable was a bar graph.Chi square test was done to check the association, and a p-value of 0.05 was said to be statistically significant.RESULTS AND DISCUSSION: 44% chose less than 60 minutes as the ideal time for replantation of an avulsed tooth. 33% of IVth year students reported 4 weeks as the splinting period for an avulsed tooth with a dry time of more than 60 minutes. 30% of IVth year students reported semi rigid as the type of splint used in the replantation of an avulsed tooth. 32% of IVth year students reported extra alveolar dry time as the most critical factor in the outcome of the replanted tooth. Association between the study year and the awareness on the splinting period of an avulsed tooth with a dry time of 60 mins(p=0.00), replantation of primary tooth(p=0.028), type of used in replantation of tooth(p=0.00), and the critical factor in the outcome of replanted tooth(p=0.00) showed a statistically significant difference.CONCLUSION: The present study reveals the knowledge and awareness among the dental students on the management of avulsed tooth.The results of this survey show that the majority were the IVth year students who were aware about the tooth avulsion, its replantation and treatment than the Ist year, IInd year, IIIrd year and Vth year students